1998
DOI: 10.1152/jappl.1998.84.6.1926
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and ventilatory responses during sleep in children with obstructive sleep apnea

Abstract: Abnormal central regulation of upper airway muscles may contribute to the pathophysiology of the childhood obstructive sleep apnea syndrome (OSAS). We hypothesized that this was secondary to global abnormalities of ventilatory control during sleep. We therefore compared the response to chemical stimuli during sleep between prepubertal children with OSAS and controls. Patients with OSAS aroused at a higher PCO2 (58 +/- 2 vs. 60 +/- 5 Torr, P < 0.05); those with the highest apnea index had the highest arousal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 25 publications
5
73
2
3
Order By: Relevance
“…We have previously demonstrated that children with OSAS had blunted arousal responses to hypercapnia (29), and impaired arousal responses to inspiratory loading during sleep compared with control subjects (16) but had a similar acoustic arousal threshold (30). This study, using a more sophisticated measure of respiratory and auditory processing stimuli, has confirmed our previous findings.…”
Section: Aep During Sleepsupporting
confidence: 86%
“…We have previously demonstrated that children with OSAS had blunted arousal responses to hypercapnia (29), and impaired arousal responses to inspiratory loading during sleep compared with control subjects (16) but had a similar acoustic arousal threshold (30). This study, using a more sophisticated measure of respiratory and auditory processing stimuli, has confirmed our previous findings.…”
Section: Aep During Sleepsupporting
confidence: 86%
“…However, most patients with OSA have arousal thresholds that are within the normal range after therapy (1,6). In those who have high arousal thresholds despite CPAP treatment (z25% of the patoents with OSA we studied), OSA is typically very severe (6,7). Increased arousal thresholds in these patients may be inherent or slowly/incompletely reversible.…”
Section: From the Authorsmentioning
confidence: 95%
“…In the current study, both CO 2 and subatmospheric pressure application resulted in increased flow and a change from a flow-limited to a nonflow-limited pattern. This was probably due to stimulation of the CNS, resulting in augmentation of upper airway neuromotor tone (7,34,35). Previously, we showed that children with OSAS had normal ventilatory responses to hypoxia and hypercapnia during both wakefulness (36) and sleep (35).…”
Section: Neuromotor Control Of the Upper Airwaymentioning
confidence: 95%
“…The neuromotor theory is supported by the literature. Previous studies have shown normalization of arousal responses to hypercapnia following T&A in children (35). In addition, adults with OSAS have an improvement in the hypercapnic ventilatory drive following tracheostomy (41), and have improvement in upper airway sensation following CPAP administration (42).…”
Section: Neuromotor Causesmentioning
confidence: 99%